Politeness in the Podcast of Shireen Sungkar and Oki Setiana Dewi Episode "The In-Law Story Makes You Cry" - Houtman, Houtman; Sakdiah Wati; Monalisa (Southeast Asian Language and Literature Studies, 2024)
The research aims to describe variations in language politeness when interactions occur between speakers and speech partners in the Shireen Sungkar and Oki Setiana Dewi Podcast Episode "Cerita Mertua Makes Me Nangis". The method used in this research is a descriptive qualitative method which in principle describes the manifestation of compliance with the principles of language politeness in the Shireen Sungkar and Oki Setiana Dewi podcast Episode of the Story of My Mother-in-law Makes Me Nangis. The data source for this research is the Shireen Sungkar and Oki Setiana Dewi Podcast on the YouTube channel The Sungkars. The data collection technique in this research is the viewing and writing technique, namely watching the podcast or object being studied and then recording all the conversations in the podcast dialogue that is spoken. The results of this research show politeness in language and contain 10 maxims of Geoffrey Leech's theory in the podcast between Shireen Sungkars and Oki Setiana Dewi, totaling 47 utterances. The podcast has been analyzed based on indicators of language politeness, so it is concluded that all the speech is included in compliance with language politeness, there is not a single speech that is a violation of language politeness because all the speech is included in the polite and very polite categories, of which there are 41 speeches and categories in the polite category. very polite there are 6 utterances. Not a single utterance was found that fell into the category of impolite or very impolite.